1998
DOI: 10.1177/0730888498025004003
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Solidarity

Abstract: In a time of economic depression and racism more overt than anything we now experience, the unions of the Congress of Industrial Organizations (CIO) during the 1930s and 1940s forged a lasting interracial solidarity within the industrial working class. The authors tell the stories of how three CIO organizing drives achieved interracial solidarity. In 1933, the United Mine Workers (UMW) adopted the “UMW formula” for placing Black workers in positions as union officers and organizers. Adopted from more radical u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Data were collected from print and video documentation of the initiatives and semistructured interviews with at least one evaluator and one program member per case (in total, 9 interviews, 119 documents, and 13 video files). Each case was analyzed separately by the principal investigator, using inductive coding in NVivo within an overarching, common coding framework, combined with an adapted form of event structure analysis (e.g., Brueggemann & Boswell, 1998; Stevenson, Zinzow, & Sridharan, 2003). The focus of data collection and analysis was on “turning point events” or process transition points and case trajectory.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected from print and video documentation of the initiatives and semistructured interviews with at least one evaluator and one program member per case (in total, 9 interviews, 119 documents, and 13 video files). Each case was analyzed separately by the principal investigator, using inductive coding in NVivo within an overarching, common coding framework, combined with an adapted form of event structure analysis (e.g., Brueggemann & Boswell, 1998; Stevenson, Zinzow, & Sridharan, 2003). The focus of data collection and analysis was on “turning point events” or process transition points and case trajectory.…”
Section: Methodsmentioning
confidence: 99%
“…Event Structure Analysis, or ESA for short (Corsaro & Heise, 1990;Griffin, 1993;Griffin & Korstad, 1998;Heise, 1989;Heise & Durig, 1997;Freitas et al, 2021), was developed as a qualitative methodology for analyzing narratives in order to reduce the action schemes that are implicit in them. The methodology, implemented in a computer program called Ethno 7 , has been applied in ethnography (Corsaro & Heise, 1990;Eder & Enke, 1991;Ponti, 2010), history (Brown, 2000;Brown & Brueggemann, 1997;Brueggemann & Boswell, 1998;Brueggemann & Brown, 2003;Griffin et al, 1997;Griffin & Korstad, 1996;Isaac et al, 1994;Richardson, 2009), organizational studies (O'Neill et al, 2007;Stevenson & Greenberg, 1998, 2000Stevenson et al, 2008), and folkloristics (Heise, 1988;Uehara, 2001).…”
Section: Event Structure Analysismentioning
confidence: 99%
“…Research in the United States found that increasingly unionized sectors of the economy are more likely to strike (Cornfield 1991;Wallace et al 1989). Other work found that repertoires of militant collective action are also more likely when union members have a precarious employment situation (Brueggemann and Boswell 1998;Dubofsky and Tine 1977). These insecure working conditions force unions to become more confrontational, reflecting the established cultural practices and solidarities of workers (Voss 1993).…”
Section: Existing Research Examining Determinants Of Strike Activitymentioning
confidence: 99%